Konsep Pendidikan Akhlak (Studi Pemikiran Ibnu Miskawaih dalam Kitab Tahzîb al-Akhlāq) - Moslem Moslem (Journal of Islamic Education Policy, 2017)
ABSTRACT Talking about the concept of morals, is something that can not be ignored just so much more to provide enlightenment for the students or educators in the field of moral education in particular. The figure of Ibn Miskawayh (his famous name) is one of the most important classical Muslim thinkers in the field of morals. He contributes greatly in drawing concrete formulations about the human soul or more precisely about the faculties of the human soul that help humans develop their moral potential. He examines morality very detailed, both on the theoretical and practical level, so that the concept is more of a rational ethic or ethical philosophy. This paper on the one hand wants to clarify the concept of moral education according to Ibn Miskawayh in his essay Tahzîb al-Akhlāq, on the other hand wants to clarify his life journey and the background of the writing of Tahzîb al-Akhlāq.Keywords: Moral education, Ibnu Miskawaih, Tahzîb al-Akhlāq